Evaluating the cyber security skills gap relating to penetration testing - Beukes, Dirk Johannes (Rhodes University, Faculty of Science, Department of Computer Science, 2021)
Information Technology (IT) is growing rapidly and has become an integral part of daily life. It provides a boundless list of services and opportunities, generating boundless sources of information, which could be abused or exploited. Due to this growth, there are thousands of new users added to the grid using computer systems in a static and mobile environment; this fact alone creates endless volumes of data to be exploited and hardware devices to be abused by the wrong people. The growth in the IT environment adds challenges that may affect users in their personal, professional, and business lives. There are constant threats on corporate and private computer networks and computer systems. In the corporate environment companies try to eliminate the threat by testing networks making use of penetration tests and by implementing cyber awareness programs to make employees more aware of the cyber threat. Penetration tests and vulnerability assessments are undervalued; are seen as a formality and are not used to increase system security. If used regularly the computer system will be more secure and attacks minimized. With the growth in technology, industries all over the globe become fully dependent on information systems in doing their day-to-day business. As technology evolves and new technology becomes available, the bigger the risk becomes to protect against the dangers which come with this new technology. For industry to protect itself against this growth in technology, personnel with a certain skill set is needed. This is where cyber security plays a very important role in the protection of information systems to ensure the confidentiality, integrity and availability of the information system itself and the data on the system. Due to this drive to secure information systems, the need for cyber security by professionals is on the rise as well. It is estimated that there is a shortage of one million cyber security professionals globally. What is the reason for this skills shortage? Will it be possible to close this skills shortage gap? This study is about identifying the skills gap and identifying possible ways to close this skills gap. In this study, research was conducted on the cyber security international standards, cyber security training at universities and international certification focusing specifically on penetration testing, the evaluation of the need of industry while recruiting new penetration testers, finishing with suggestions on how to fill possible gaps in the skills market with a conclusion.
Keywords: Computer networks -- Security measures; Computer networks -- Monitoring; Computer networks -- Management; Data protection; Information technology -- Security measures; Professionals -- Supply and demand; Electronic data personnel -- Supply and demand